2016
DOI: 10.1642/auk-15-128.1
|View full text |Cite
|
Sign up to set email alerts
|

Darker eggshell spotting indicates lower yolk antioxidant level and poorer female quality in the Eurasian Great Tit (Parus major)

Abstract: Protoporphyrin pigment causes the red-brown eggshell colors; however, for many species, the function of this pigment is unknown. It has been proposed that eggshell pigmentation may strengthen the shell or that it may be a sexually selected signal, which advertises the quality of the female and that of her offspring to the male parent. In this study, we aimed to discover whether protoporphyrin-based eggshell pigmentation patterns of Eurasian Great Tits (Parus major) were related to female or egg quality. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 89 publications
5
33
1
Order By: Relevance
“…In great tits Parus major, it has been found that females with lower body mass laid eggs with darker eggshell spotting (Stoddard et al 2012). In addition, great tit females laying smaller clutches, an indicator of either lower intrinsic quality or poorer quality territory with lower food availability (Hargitai et al 2016b), and females that bred when caterpillar availability was lower, laid eggs with darker spots (Hargitai et al 2016c). These studies support the view that darker eggshell protoporphyrin pigmentation indicates lower maternal body condition and poorer food availability.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In great tits Parus major, it has been found that females with lower body mass laid eggs with darker eggshell spotting (Stoddard et al 2012). In addition, great tit females laying smaller clutches, an indicator of either lower intrinsic quality or poorer quality territory with lower food availability (Hargitai et al 2016b), and females that bred when caterpillar availability was lower, laid eggs with darker spots (Hargitai et al 2016c). These studies support the view that darker eggshell protoporphyrin pigmentation indicates lower maternal body condition and poorer food availability.…”
Section: Introductionsupporting
confidence: 54%
“…In great tits, it was reported that females laying smaller clutches, an indicator of either lower intrinsic quality or poorer quality territory with lower food availability (Hargitai et al 2016b), and females that bred early in the breeding season when caterpillar availability was lower, laid eggs with darker spots (Gosler et al 2000, Brulez et al 2014, Hargitai et al 2016c. Moreover, Honza et al (2012) demonstrated that great reed warblers Acrocephalus arundinaceus laid darker eggs in colder weather.…”
Section: Brown Eggshell Pigmentationmentioning
confidence: 99%
“…We found that birds that bred earlier in the reproductive season laid eggs with darker spots, suggesting higher allocation of protoporphyrin pigments to the eggshell (Brulez et al 2014;Hargitai et al 2016b). Additionally, we found that in colder weather and when breeding in higher density areas birds laid eggs with more spotting.…”
Section: Breeding Density (Pair/100 M Radius Circle)mentioning
confidence: 82%
“…The other spotting variables were weakly correlated (size-distribution r = 0.12, N = 268, P = 0.05) or showed no significant correlation (intensity-coverage r = -0.03, P = 0.68; size-coverage r = 0.08, P = 0.20; intensity-distribution r = -0.06, P = 0.34, all N = 268). It has been previously shown that eggshell protoporphyrin concentration in Great Tit eggs positively correlates with spot intensity, spot size, and spotting coverage, but does not correlate with spot distribution (Brulez et al 2014;Hargitai et al 2016b). We decided not to apply a principal component analysis (PCA), but instead to use the original scored variables in the statistical analyses.…”
Section: Eggshell Pigmentation Scoringmentioning
confidence: 99%
See 1 more Smart Citation